Dampak Transformasi Kompetensi Amil terhadap Keberlanjutan Pemberdayaan pada Program Microfinance Syariah Berbasis Masyarakat - Irfan , Irfan; Zam Zami, Muhammad Faisal (Islamic Management and Empowerment Journal, 2026)
This study aims to analyze the impact of transforming amil competencies on the sustainability of community empowerment through the Misykat program at LAZ DT Peduli Bogor. The research provides theoretical contributions to dawah management and practical references for zakat institutions in optimizing amil's role as agents of social change. A qualitative descriptive method with a case study approach was employed, utilizing inductive analysis procedures. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that transforming amil competencies in managerial aspects, public speaking skills, and the internalization of FAST values (Siddiq, Amanah, Tabligh, Fathonah) significantly impacts mustahik's economic and spiritual independence. Empowerment sustainability is achieved through intensive mentoring, which remains effective despite core personnel limitations due to strategic synergy with student volunteers.